Нетрговски бариери во мултилатералниот трговски систем - Серсемов, Благој (Економски факултет, УКИМ, Скопје, 2019)
Non-trade barriers in trade of goods are not a trade instrument at all. They are implemented in order to regulate other areas than trade, but once they are introduced, they produce a strong restrictive effect upon the export or import of goods. Countries use the right to implement such measures in order to protect human lives or the health and welfare of all leaving beings within their national economies. Non-trade barriers to trade are obstacles in international trade which frustrate entrepreneurs. They are also known as invisible barriers because they are difficult to be discovered. They are not regulated within the WTO and their implementation does not impose sanctions in most of the cases. Due to the common use and constant creation of new non-trade barriers to trade, it is very hard and complicated to classify new non-trade barriers to trade. The international classification of new non-trade barriers to trade was introduced by UNCTAD and the main division of these barriers comprises technical barriers in trade, sanitary and phyto-sanitary barriers and administrative barriers. The doctoral thesis includes an analysis of the classic as well as the new non-trade barriers in trade. This aim was realized by processing primary, secondary and tertiary literature from relevant databases. The analysis of relevant data basis in the Republic of Macedonia was additionally enriched by creating a questionnaire completed by 60 domestic firms involved in export-import activities. Data from the questionnaire were processed with the help of descriptive statistical methods, and results gained thereof were presented graphically or in tables. The summary of the results of the research in the thesis confirmed that the new non-trade barriers are used more and more by the big traders, but also from the underdeveloped economies as new protectionist measures in trade of goods.
Докторска дисертација одбранета во 2019 година на Економскиот факултет во Скопје, под менторство на проф. д–р Ирена Кикеркова.
Keywords: multilateral trade system, EU, the Republic of Macedonia, non-trade barriers in trade, technical barriers, sanitary and phytosanitary measures; administrative barriers